Prevalence and Antimicrobial-Resistant Features of Shigella Species in East Africa from 2015–2022: A Systematic Review and Meta-Analysis - Basha Ayele; Getenet Beyene; Mekdelawit Alemayehu; Aman Dekebo; Zeleke Mekonnen; Gashaw Nigussie (Interdisciplinary Perspectives on Infectious Diseases)
Background. Shigellosis is the most common cause of epidemic dysentery found worldwide, particularly in developing countries, where it causes infant diarrhea and mortality. The prevalence of Shigella species resistant to commonly used antimicrobial drugs has steadily increased. The purpose of this review is to describe the prevalence and antimicrobial resistance (AMR) characteristics of Shigella species in East Africa between 2015 and 2022. Methods. Studies were identified using a computerized search of Medline/PubMed, Google Scholar, and Web of Science databases, with a detailed search strategy and cross-checking of reference lists for studies published between 2015 and 2022. Articles presenting data on prevalence and AMR, accessibility of the full-length article, and publication dates between 2015 and 2022 were the eligibility criteria for inclusion in the review. Original research reports written in English were considered. The heterogeneities of the studies were examined, and a meta-analysis was performed to estimate the pooled prevalence and AMR using a random effects model. Results. The pooled prevalence of Shigella species in East Africa was 6.2% (95% CI −0.20–12.60), according to an analysis of 22 studies. Shigella species prevalence was 4.0% in Ethiopia, 14.6% in Kenya, 0.7% in Sudan, 5.2% in South Sudan, and 20.6% in Somalia. The association of Shigella infection significantly varied among the countries (p=0.01). Among the antibiotics tested, most Shigella isolates were susceptible to ciprofloxacin, norfloxacin, nalidixic acid, and ceftriaxone. Despite the fact that the reports varied in study sites and time, Shigella species were resistant to tetracycline, ampicillin, amoxicillin, chloramphenicol, and co-trimoxazole. Conclusion. The pooled estimate indicates high burden of Shigella infection in East Africa, as well as a high proportion of drug resistance pattern to tetracycline, ampicillin, chloramphenicol, and amoxicillin. Therefore, initiating and scale-up of performing drug susceptibility test for each shigellosis case need to be considered and strengthened.